(untitled) (Anais do Congresso Brasileiro de Processo Coletivo e Cidadania, 2024)
The present work discussed the popular action on the constitutional bias, mainly addressing the democratic principle and the principle of popular sovereignty. It aimed to demonstrate that popular action is an effective instrument for the control of public affairs and public morality through the Judiciary. He highlighted that this instrument represents an exercise of participatory democracy, in which the people themselves exercise power. Using an exploratory-bibliographic research, guided by the analytical-deductive method. As a result, it was found that the 1988 Constitution of the Federative Republic of Brazil admits participatory democracy, that is, it allows the people to participate in the government in their own interest based on popular sovereignty. In this way, the Brazilian citizen will be able to supervise the entire Administration in a broad sense, guided by its morality and probity and, in this way, contribute to maintaining the integrity of the system. Achieving such pretensions means acting with citizenship in addition to cooperating so that the democratic regime guarantees freedom, equality and the dignity of the human person, these being the main values of democracy. Thus, it remains demonstrated that popular action is a powerful instrument that should be more used by Brazilian citizens in order to realize true democracy in Brazilian society.